The Business of Creative Industries - CHONG, Mark, (Institutional Knowledge at Singapore Management University, 2015)
Creative industries worldwide are an important driver of economic growth and cultural influence. In addition to creating numerous jobs for the economy, creative industries can also shape public perception of countries, regions and cities (and hence place brand). Singapore, too, understands the potential for creative ideas to transform the economy. Among its more high-profile projects include attracting Lucasfilm and video gaming giant Ubisoft to set up base in the country.